Autosomal recessive mutations in THOC6 cause intellectual disability: syndrome delineation requiring forward and reverse phenotyping. Issue 1 (24th May 2016) - Amos, J.S.; Huang, L.; Thevenon, J.; Kariminedjad, A.; Beaulieu, C.L.; Masurel‐Paulet, A.; Najmabadi, H.; Fattahi, Z.; Beheshtian, M.; Tonekaboni, S.H.; Tang, S.; Helbig, K.L.; et al.
Abstract : THOC6 is a part of the THO complex, which is involved in coordinating mRNA processing with export. The THO complex interacts with additional components to form the larger TREX complex (transcription export complex). Previously, a homozygous missense mutation in THOC6 in the Hutterite population was reported in association with syndromic intellectual disability. Using exome sequencing, we identified three unrelated patients with bi‐allelic mutations in THOC6 associated with intellectual disability and additional clinical features. Two of the patients were compound heterozygous for a stop and a missense mutation, and the third was homozygous for a missense mutation; the missense mutations were predicted to be pathogenic by in silico analysis and modeling. Clinical features of the three newly identified patients and those previously reported are reviewed; intellectual disability is moderate to severe, and malformations are variable including renal and heart defects, cleft palate, microcephaly, and corpus callosum dysgenesis. Facial features are variable and include tall forehead, short upslanting palpebral fissures +/− deep set eyes, and a long nose with overhanging columella. These subtle facial features render the diagnosis difficult to make in isolation with certainty. Our results expand the mutational and clinical spectrum of this rare disease, confirm that THOC6 is an intellectual disability causing gene, while providing insight into the importance of the THO complex in neurodevelopment. Abstract :